On the Effect of Focusing of Coherent Diffraction Radiation by a Semi-Parabolic Target; Physics of Particles and Nuclei Letters; Vol. 21, iss. 2 - Potylitsyn A. P. Alexander Petrovich; Vukolov A. V. Artem Vladimirovich; Shevelev M. V. Mihail Viktorovich; Baldin A. A. Anton Aleksandrovich; Bleko V. V. Vladislav Vitoldovich; Bleko V. V. Vitold Vladislavovich; Kobets V. V. Valery Vasiljevich; Karataev P. V. Pavel Vladimirovich; Kocharian (Kocharyan) V. R. Vagan Rashidovich (2024, 2024)
Title screen